Recognition of Customary Disputes Settlement in Law Number 6 of 2014 on Villages: A Responsive Law Review in Indonesian Legal Reform - Winarsih, Winarsih (Universitas Negeri Semarang, 2017)
Based on the development of the community's need for legal certainty on customary dispute settlement, Law No. 6 of 2014 on the village which gives authority to adat villages to resolve customary law dispute prevailing in adat village as long as it is in harmony with the principle of human rights by prioritizing the settlement by deliberation. In addition, adat villages are also given the authority to arry out an indigenous village justice peace trial. This normative recognition authorizes adat villages to apply the values or norms that have been lived and developed in the community closely related to the responsive law proposed by Philippe Nonet and Philip Selznick stating that responsive law is born from legal realism in society so that it appears laws that are more responsive to socialneeds. This paper discusses adat dispute resolution in Law No. 6 of 2014 on Village in the review of Responsive Law in Indonesian Legal Reform.